Measuring the non-observed economy : a handbook (Statistics (Organisation for Economic Co-operation and Development), 2002)
This essential Handbook makes underground, hidden, grey economies intelligible and consistently quantifiable. An invaluable tool for statistics producers and users and researchers, the book explains how the non-observed economy can be measured and comments on the reliability of and differences between various methods. The purpose of this Handbook is to identify and promote best practice consistent with international standards like the 1993 System of National Accounts.